2010
DOI: 10.1016/j.carj.2009.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Local Recurrence and Radiofibrosis by Computed Tomography Perfusion on Nasopharyngeal Carcinoma after Radiotherapy

Abstract: The results demonstrate that perfusion CT is a reliable and accurate method to identify LR and RF after radiotherapy in patients with nasopharyngeal carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…Of these, 15 articles were written in languages other than English (including Chinese [ n = 5], French [ n = 2], German [ n = 2], Italian [ n = 3], Japanese [ n = 2], and Polish [ n = 1]). Eighty‐eight were excluded during full review (see Figure ), and 4 met our inclusion criteria . Five additional articles were identified via hand searching (1 from our laboratory's reference database, 3 via searching references from accepted papers, and 1 that was known to the authors).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 15 articles were written in languages other than English (including Chinese [ n = 5], French [ n = 2], German [ n = 2], Italian [ n = 3], Japanese [ n = 2], and Polish [ n = 1]). Eighty‐eight were excluded during full review (see Figure ), and 4 met our inclusion criteria . Five additional articles were identified via hand searching (1 from our laboratory's reference database, 3 via searching references from accepted papers, and 1 that was known to the authors).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 9 accepted articles, 3 included only patients with nasopharyngeal cancer, 1 included only patients with oropharyngeal cancer, 4 included multiple head and neck cancer sites, and in 1, sites were unreported (see Table ). With respect to cancer severity, 3 studies included patients with early and late‐stage cancers, 1 study included only late‐stage cancers, and in 5, severity was unreported . Cancer histology was only reported in 3 studies, 2 of which included patients with squamous cell carcinoma and 1 that included patients with either adenoid cystic or mucoepidermoid carcinoma .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the optimal mathematical model to quantify perfusion and diffusion characteristics is still unclear (138). Similar to DCE-MRI, perfusion CT assesses the temporal changes in tumour attenuation after intravenous iodinated contrast administration, allowing estimation of intratumoral blood flow, blood volume and vessel permeability (143,144). Although sequential PET and functional MRI/CT can be performed on different occasions, near simultaneous acquisitions of PET and MRI/ CT will be advantageous in terms of patient convenience and minimising the effect of temporal heterogeneity between scans.…”
Section: Future Directionsmentioning
confidence: 99%
“…Carcinoma: Modern technologies of CT in nasopharyngeal carcinoma include perfusion imaging (CTP) and virtual endoscopy (CTVE),which are increasingly used in clinical diagnosis The technology of CTP utilizes perfusion parameters (such as :blood perfusion , blood volume and so on) to get an image which shows vascular characteristics and hemodynamic changes in nasopharyngeal lesion It can find more early recurrent nasopharyngeal carcinoma lesions than conventional CT Jin et al [3] found the technology of CTP can provide timely hemodynamic changes in the physiological and pathological situations and evaluate the efficacy of the treatment process, it can also further infer biological characteristics of the tumor and prognosis [4] Meanwhile, studies from Liu et al [5] also showed that multi-slice spiral CT can more clearly reflect the tumor blood flow, [6] found…”
Section: New Ct Techniques and Diagnostic For Nasopharyngealmentioning
confidence: 99%